KUTA PARIT DESA ZERO STUNTING: STRATEGI SUKSES MENGANTISIPASI STUNTING SEJAK DINI - Alfarido, Muhammad; Siagian, Nazwa Chairunnisa Hamid; Yasri, Bayhaqi; Sugiantoro, Bambang Heri; Lubis, Zulpahmi (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Stunting prevention socialization is one of the important efforts to improve the nutritional quality of pregnant women and toddlers. This study aims to determine the village government’s strategy, the role of Posyandu cadres, the support of midwives, and the participation of parents in the zero stunting program in Kuta Parit Village. The method used was qualitative interviews with key informants including the village head, village officials, Posyandu cadres, village midwives, sub-district health workers, and parents of toddlers, as well as field observations during the socialization activities. The results showed that the main strategy of the village was the provision of supplementary food (PMT) and nutrition education for pregnant women and toddlers, supported by village fund allocation and regular coordination with the community health center (puskesmas). Posyandu cadres played a role in routine monitoring and nutrition education, while midwives provided nutrition consultations and regular pregnancy check-ups. Parents of toddlers acknowledged the benefits of PMT, cadre guidance, and student community service (KKN) socialization in increasing their knowledge about balanced nutrition and stunting prevention. Based on these findings, the stunting prevention program in the village can be strengthened through enhanced socialization, cadre training, and cross-sectoral coordination.